Evaluation academic website using Kansei Engineering / Ahmad Luqman Ahmad Firdaus - Ahmad Firdaus, Ahmad Luqman (2016)
Past literature had mention that emotion plays an important role in capturing visitor's attention into the website. Although currently design requirement that supports academic website, design requirement in developing academic website which embeds emotion is currently not many is available. In this study, Kansei Engineering will be used to embeds emotion in academic website. This study represents on how to formulate design requirement that could develop academic website that embeds emotion. This experiment is conducted using 5-SD scale form using 6 keywords that had been finalized based on website from top ranking university. Later, the data was analyzed using PC Analysis, Factor Analysis (FA) and Partial Least Square Analysis(PLS) to proposed new design guide for academic websites. In this study, the objectives are able to identify the emotion structure in academic website, the influence of design elements and to propose design guide that embeds target emotion in academic website. The main significant for this study goes to website designer in developing academic website based on the design requirement provided. By following the design guide prepared, the website could attract related people especially the group of academic researchers. As a result of this study, emotion structure and the influence of design element in academic website had been identified and the design guide to enables target emotion in academic website are also proposed in this study.